A Two-Level Cache for Distributed Information Retrieval in Search Engines - Weizhe Zhang; Hui He; Jianwei Ye (The Scientific World Journal)
To improve the performance of distributed information retrieval in search engines, we propose a two-level cache structure based on the queries of the users’ logs. We extract the highest rank queries of users from the static cache, in which the queries are the most popular. We adopt the dynamic cache as an auxiliary to optimize the distribution of the cache data. We propose a distribution strategy of the cache data. The experiments prove that the hit rate, the efficiency, and the time consumption of the two-level cache have advantages compared with other structures of cache.